Association Between Prenatal Exposure to Bacterial Infection and Risk of Schizophrenia - Holger J. Sørensen; Erik Lykke Mortensen; June Machover Reinisch; S. A. Mednick (2008)
Recent research suggests that prenatal exposure to nonviral infection may be associated with increased risk of schizophrenia, and we hypothesized an association between maternal bacterial infection during pregnancy and elevated offspring risk of schizophrenia. Data on maternal infections from the Copenhagen Perinatal Cohort were linked with the Danish National Psychiatric Register. Offspring cases of narrowly defined schizophrenia (International Classification of Diseases, Eighth Revision [ICD-8]) and more broadly defined schizophrenia (ICD-8 and ICD-10) were identified before the ages of 32-34 and 45-47 years, respectively. The effect of prenatal exposure to bacterial infections was adjusted for prenatal exposure to analgesics and parental social status. In a risk set of 7941 individuals, 85 cases (1.1%) of ICD-8 schizophrenia were identified by the age of 32-34 years and 153 cases (1.9%) of more broadly defined schizophrenia by the age of 45-47 years. First-trimester exposure conferred an elevated risk of ICD-8 schizophrenia (odds ratio 2.53; 95% confidence interval [CI] 1.07-5.96) and also of broadly defined schizophrenia (odds ratio 2.14; 95% CI 1.06-4.31). Second-trimester exposure also conferred a significantly elevated risk of schizophrenia but only in unadjusted analyses. These findings suggest a relationship between maternal bacterial infection in pregnancy and offspring risk of schizophrenia, and this effect was somewhat stronger for ICD-8 schizophrenia with earlier onset. Post hoc analyses showed that upper respiratory tract and gonococcal infections were associated with elevated risk of the disease. An association between risk of schizophrenia and prenatal exposure to bacterial infections might be mediated through transplacental passage of maternally produced cytokines in response to bacterial infections.